2005
DOI: 10.1021/es0483692
|View full text |Cite
|
Sign up to set email alerts
|

Cr(VI) Reduction and Immobilization by Magnetite under Alkaline pH Conditions:  The Role of Passivation

Abstract: This study investigated Cr(VI) reduction and immobilization by magnetite under alkaline pH conditions similar to those present at the Hanford site. Compared to acidic and neutral pH, chromium(VI) reduction by magnetite at high pH conditions is limited (<20% of potential reduction capacity), and the extent of reduction does not vary significantly with increasing NaOH concentration. This is due to the formation of maghemite, goethite, and/or Fe1-xCrxOOH, which may form a passivation layer on the magnetite surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
90
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(105 citation statements)
references
References 29 publications
15
90
0
Order By: Relevance
“…These results are consistent with the formation of a passivating layer during metal reduction. [32][33][34] Nanoparticulate UO 2 growth rates observed by AFM are consistent with U(VI) reduction rates determined by the GI-XANES analysis; the U L III -edge position moves to lower energy values within 2-4 hours after exposure of U(VI) to the magnetite (111) surface (Fig. 2) but reached a plateau around 8 hours, roughly the same time that the AFM data indicated slowing precipitate formation.…”
Section: Nanoparticulate Uo 2 Growth and U(vi) Reduction Ratessupporting
confidence: 81%
“…These results are consistent with the formation of a passivating layer during metal reduction. [32][33][34] Nanoparticulate UO 2 growth rates observed by AFM are consistent with U(VI) reduction rates determined by the GI-XANES analysis; the U L III -edge position moves to lower energy values within 2-4 hours after exposure of U(VI) to the magnetite (111) surface (Fig. 2) but reached a plateau around 8 hours, roughly the same time that the AFM data indicated slowing precipitate formation.…”
Section: Nanoparticulate Uo 2 Growth and U(vi) Reduction Ratessupporting
confidence: 81%
“…No dissolved Cr(III) was detected during the reaction, which suggests that all the Cr(III) was co-precipitated with Fe(III). This observation is consistent with those reported previously (Williams and Scherer 2001;He and Trainas 2005). It can be concluded that iron hydroxide and chromium hydroxide could be the final and predominant products of Cr(VI) reduction by CMC-stabilized Fe 0 nanoparticles.…”
Section: Resultssupporting
confidence: 93%
“…This passivation reaction converts metallic iron to a composite oxyhydroxide of iron(III)-chromium(III) with low electrical conductivity that prevents passage of electrons from Fe(0) to Cr(VI). Similar passivation has been reported during reduction by magnetite also (He and Traina 2005).…”
Section: Introductionsupporting
confidence: 82%